2015
DOI: 10.5465/amp.2013.0121
|View full text |Cite
|
Sign up to set email alerts
|

Linking Workplace Practices to Community Engagement: The Case for Encouraging Employee Voice

Abstract: Research on employee voice suggest that providing employees with the sense that it is safe to speak up to their managers about their concerns, ideas, and suggestions can have very positive effects on employee behavior inside organizations. Here, we argue that providing employees with voice opportunities is also likely to be essential in building "positive" organizations that contribute to the building of human potential in our communities and societies.Specifically, we argue that employees who perceive that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 76 publications
0
51
0
2
Order By: Relevance
“…Voice capability can spill over to promoting more active participation in society and supporting democratic political processes and social harmony (Milliken, Schipani, Bishara, & Prado 2015;Spreitzer, 2007). Indeed, as suggested in this Symposium, to the extent that employees have the opportunity to exercise their voice and express their opinions in the business organization, there is likely to be a positive spillover effect to other aspects of their lives (Milliken et al, 2015).…”
Section: Peacebuilding Activitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Voice capability can spill over to promoting more active participation in society and supporting democratic political processes and social harmony (Milliken, Schipani, Bishara, & Prado 2015;Spreitzer, 2007). Indeed, as suggested in this Symposium, to the extent that employees have the opportunity to exercise their voice and express their opinions in the business organization, there is likely to be a positive spillover effect to other aspects of their lives (Milliken et al, 2015).…”
Section: Peacebuilding Activitiesmentioning
confidence: 93%
“…Voice capability can spill over to promoting more active participation in society and supporting democratic political processes and social harmony (Milliken, Schipani, Bishara, & Prado 2015;Spreitzer, 2007). Indeed, as suggested in this Symposium, to the extent that employees have the opportunity to exercise their voice and express their opinions in the business organization, there is likely to be a positive spillover effect to other aspects of their lives (Milliken et al, 2015). Whether this is a result of congruence-that a person interested in exercising voice will find both employment and other activities congruent with his personality and preferences or whether the exercise of voice is a result of skill-building at work that has impact elsewhere-the correlation between them suggests that something valuable occurs when employees do, in fact, exercise voice at work (Milliken et al, 2015).…”
Section: Peacebuilding Activitiesmentioning
confidence: 99%
“…Janssen and Gao (2015) found among 337 supervisor-subordinate dyads in the Chinese manufacturing industry that when employees perceive that they have high voice status, they are motivated to engage in subsequent voice behavior (see also Ohana, 2016). Employee voice can also be an important component of psychological safety in the workplace because it provides employees with a safe climate (Milliken et al, 2015). When employee voice opportunities are absent or shallow, research has shown an increase in withdrawal behaviors and decreased performance among employees due to perceived discrimination (Matsunaga, 2015;Wagstaff, del Carmen Triana, Kim, & Al-Riyami, 2015).…”
Section: Linking Employee Voice Mechanisms and Lgbt Expatriationmentioning
confidence: 99%
“…Employee voice has a strong research history across many fields including HRM, political science, industrial relations, and organizational behavior (Dundon, Wilkinson, Marchington, & Ackers, 2004;Milliken, Schipani, Bishara, & Prado, 2015;Mowbray, Wilkinson, & Tse, 2015;Wilkinson & Fay, 2011). Dundon et al (2004) define employee voice as 'a complex and uneven set of meanings and purposes with a dialectic shaped by external regulations, on the one hand, and internal management choice, on the other' (p. 1149).…”
Section: Introductionmentioning
confidence: 99%
“…The moment we approach people with certain questions influences them in some way. [19] claim that employee voice in a sense that people have a chance to express their wishes and concerns can have very positive effects on employee behavior. People also have more comfort and preference to journey towards the future (the unknown) when they carry forward parts of the past (the known).…”
Section: David Cooperrider and Suresh Srivastvamentioning
confidence: 99%